RETRACTED: Clematichinenoside Serves as a Neuroprotective Agent Against Ischemic Stroke: The Synergistic Action of ERK1/2 and cPKC Pathways - Liu, Chao; Du, Qianming; Zhang, Xu; Tang, Zhichao; Ji, Hui; Li, Yunman (Frontiers in Cellular Neuroscience, 2016)
There are numerous evidences suggesting that inhibition of apoptosis of neurons play a critical role in preventing the damage and even death of neurons after brain ischemia/reperfusion, which shows therapeutic potential for clinical treatment of brain injury induced by stroke. In this study, we aimed to investigate the neuroprotective effect of Clematichinenoside (AR) and its underlying mechanisms. MCAO mode was performed in rats and OGD/R model in primary cortical neurons to investigate the neuroprotective effect of AR. The rate of apoptotic cells was measured using TUNEL assay in cerebral cortex and flow cytometric assay in cortical neurons. Apoptosis-related proteins such as bcl-2, bcl-xl and bax and the phosphorylation of ERK1/2, cPKC, p90RSK, and CREB in ischemic penumbra were assayed by western blot. Furthermore, we made a thorough inquiry about how these proteins play roles in the anti-apoptotic mechanism using targets-associated inhibitors step by step. The results revealed that AR could activate both ERK1/2 and cPKC which resulted in p90RSK phosphorylation and translocation into the nucleus. Moreover, CREB, a downstream target of p90RSK, was phosphorylated and then bound to cAMP-regulated enhancer (CRE) to activate apoptosis-related genes, and finally ameliorate ischemic stroke through preventing neuron death. In conclusion, these data strongly suggest that AR could be used as an effective neuroprotective agent to protect against ischemic stroke after cerebral I/R injury through regulating both ERK1/2 and cPKC mediated p90RSK/CREB apoptotic pathways.